2013
DOI: 10.1128/aac.01039-12
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Subunit ε of the Mycobacterium tuberculosis F 1 F o ATP Synthase and a Novel Model for Mechanism of Action of the Tuberculosis Drug TMC207

Abstract: dThe subunit of bacterial F 1 F O ATP synthases plays an important regulatory role in coupling and catalysis via conformational transitions of its C-terminal domain. Here we present the first low-resolution solution structure of of Mycobacterium tuberculosis (Mt) F 1 F O ATP synthase and the nuclear magnetic resonance (NMR) structure of its C-terminal segment (Mt 103-120 ). Mt is significantly shorter (61.6 Å) than forms of the subunit in other bacteria, reflecting a shorter C-terminal sequence, proposed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 45 publications
3
87
0
Order By: Relevance
“…This correlates with results of recent computational studies of coevolution in protein complexes, which used interactions of ␥ and ⑀ as a test case (63,64). There are also indications that ⑀ inhibition also occurs in the enzyme of several species of Mycobacterium (65,66), and the CTD of most mycobacterial ⑀ subunits is ϳ17 residues shorter than that of E. coli, although different possible alignments make it uncertain how much of the hook and/or helix-2 are absent (67,68). Mycobacterial ATP synthase is the target of a new class of antibiotics, the diarylquinolines, and the lead drug, bedaquiline, has been approved for treatment of multidrug-resistant tuberculosis (25,69).…”
Section: Discussionsupporting
confidence: 82%
“…This correlates with results of recent computational studies of coevolution in protein complexes, which used interactions of ␥ and ⑀ as a test case (63,64). There are also indications that ⑀ inhibition also occurs in the enzyme of several species of Mycobacterium (65,66), and the CTD of most mycobacterial ⑀ subunits is ϳ17 residues shorter than that of E. coli, although different possible alignments make it uncertain how much of the hook and/or helix-2 are absent (67,68). Mycobacterial ATP synthase is the target of a new class of antibiotics, the diarylquinolines, and the lead drug, bedaquiline, has been approved for treatment of multidrug-resistant tuberculosis (25,69).…”
Section: Discussionsupporting
confidence: 82%
“…Bedaquiline kills M. tuberculosis by interacting with the hydrophobic region of subunit c, as well as with subunit ε (48), of the F 1 F 0 -ATP synthase and does not cross-react with the human ATP synthase complex (56,58). Inhibition of c-ring rotation due to disruption in the c-ring:ε subunit interaction results in inhibition of ATP production and subsequent cell death (48). The efficacy of bedaquiline in clinical trials confirms that targeting energy metabolism during TB infection may be promising, particularly for nonreplicating organisms, as there is documented evidence that ATP is essential for the viability of nonreplicating persistent mycobacteria (20,55,59).…”
Section: Drugs That Target the Etcmentioning
confidence: 99%
“…Rotation of subunits ε and ␥ is coupled to rotation of the c-ring upon proton translocation ( Fig. 1) (48,49). The mycobacterial F 1 F 0 -ATP synthase is encoded by a single operon, Rv1303-atpBEFHAGDC-Rv1312 (17).…”
Section: Atp Synthesis and The F 1 F 0 -Atp Synthasementioning
confidence: 99%
See 1 more Smart Citation
“…Because of its novel mechanism, bedaquiline does not have cross-resistance with current antituberculosis drugs. Many efforts have been made by scientists to locate the exact binding domain of bedaquiline in M. tuberculosis ATPase [5][6][7][8][9]. Most recently, in 2015, the X-ray crystal structures of a mycobacterial C 9 ring with and without a bedaquiline molecule were reported, and it was suggested that bedaquiline blocked the ion-binding sites of the c-subunits [10].…”
Section: Introductionmentioning
confidence: 99%